The Firm-Specific Determinants of Capital Structure in Beverage Industry in Europe - Dalci, Ilhan; Ozyapici, Hasan; Ünlücan, Do?an (Springer Science and Business Media B.V., 2019)
This study investigates the firm-specific capital structure determinants for the listed firms operating in the beverage industry in Europe. The financial data related to the period 2010–2018 are obtained from Orbis. A total of 83 companies with 747 observations are used. According to the results, profitability is negatively correlated with total debt ratio, long-term debt ratio, and short-term debt ratio. Tangibility and liquidity are also negatively correlated with both total debt ratio and short-term debt ratio. Also, it is found that growth has a statistically significant negative impact on both total debt ratio and long-term debt ratio. On the other hand, the results underline that non-debt tax-shield is positively correlated with total debt ratio and short-term debt ratio. Similarly, size is positively correlated with both total debt ratio and long-term debt ratio. To sum up, growth, tangibility, liquidity, profitability, size, and non-debt tax shield have statistically significant influences on debt ratios. This study may help managers and policy makers interested in capital structure determinants to make accurate decisions. Creditors may also utilize this study to analyze the capital structure of borrowers while they are considering the issues related to lending money. © 2019, Springer Nature Switzerland AG.
4th International Conference on Banking and Finance Perspectives, ICBFP 2019 -- 2019-05-02 through 2019-05-03 -- Famagusta -- 273729
Keywords: Beverage industry; Capital structure; Debt; Profitability